Mid-term results of anatomical total shoulder arthroplasty for primary osteoarthritis using a short-stemmed cementless humeral component - Schnetzke, Marc; Rick, S.; Raiss, Patric; Walch, G.; Loew, M. (The bone & joint journal, 2018)
AimsThe aim of this study was to evaluate the clinical and radiological outcome of using an anatomical short-stem shoulder prosthesis to treat primary osteoarthritis of the glenohumeral joint.Patients and MethodsA total of 66 patients (67 shoulders) with a mean age of 76 years (63 to 92) were available for clinical and radiological follow-up at two different timepoints (T1, mean 2.6 years, sd 0.5; T2, mean 5.3 years, sd 0.7). Postoperative radiographs were analyzed for stem angle, cortical contact, and filling ratio of the stem. Follow-up radiographs were analyzed for timing and location of bone adaptation (cortical bone narrowing, osteopenia, spot welds, and condensation lines). The bone adaptation was classified as low (between zero and three features of bone remodelling around the humeral stem) or high (four or more features).ResultsThe mean Constant score improved significantly from 28.5 (sd 11.6) preoperatively to 75.5 (sd 8.5) at T1 (p < 0.001) and remained stable over time (T2: 76.6, sd 10.2). No stem loosening was seen. High bone adaptation was present in 42% of shoulders at T1, with a slight decrease to 37% at T2. Cortical bone narrowing and osteopenia in the region of the calcar decreased from 76% to 66% between T1 and T2. Patients with high bone adaptation had a significantly higher mean filling ratio of the stem at the metaphysis (0.60, sd 0.05 vs 0.55, sd 0.06; p = 0.003) and at the diaphysis (0.65 sd 0.05 vs 0.60 sd 0.05; p = 0.007). Cortical contact of the stem was also associated with high bone adaptation (14/25 shoulders, p = 0.001). The clinical outcome was not influenced by the radiological changes.ConclusionTotal shoulder arthroplasty using a short-stem humeral component resulted in good clinical outcomes with no evidence of loosening. However, approximately 40% of the shoulders developed substantial bone loss in the proximal humerus at between four and seven years of follow-up.Cite this article: Bone Joint J 2018;100-B:603-9.
Gesehen am 08.04.2020